The Influence of Lifestyle, Product Knowledge and Product Design on Local Brand Love for Compass Shoes with Brand Image as an Intervening Variable in Surabaya - Sven Inggil Anugerah Kretarto; Nurul Azizah (International Journal of Social, Economic, and Business, 2025)
This study investigates the influence of lifestyle, product knowledge, and product design on local brand love for Compass Shoes in Surabaya, with brand image acting as an intervening variable. Utilizing a quantitative research method, data was collected from 150 Surabaya residents through questionnaires and analyzed using SEM-Partial Least Square (PLS). The findings indicate that brand image significantly influences local brand love. While lifestyle directly impacts local brand love, its influence on brand image is not significant. Product knowledge significantly affects brand image but does not directly influence local brand love. Crucially, product design significantly influences both brand image and local brand love. Furthermore, brand image mediates the relationship between product knowledge and local brand love, as well as between product design and local brand love, demonstrating that a positive brand image is crucial for fostering emotional connections with consumers. However, brand image does not mediate the relationship between lifestyle and local brand love. These results suggest that for optimal brand love, especially for brands like Compass Shoes, integrating innovative and functional product design with a strong brand image is essential.